2012
DOI: 10.1007/s12011-012-9547-x
|View full text |Cite
|
Sign up to set email alerts
|

Metal Concentrations in Cerebrospinal Fluid and Blood Plasma from Patients with Amyotrophic Lateral Sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is a progressive and fatal degenerative disorder of motor neurons. The cause of this degeneration is unknown, and different causal hypotheses include genetic, viral, traumatic and environmental mechanisms. In this study, we have analyzed metal concentrations in cerebrospinal fluid (CSF) and blood plasma in a well-defined cohort (n = 17) of ALS patients diagnosed with quantitative electromyography. Metal analyses were performed with high-resolution inductively coupled plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
121
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(133 citation statements)
references
References 276 publications
(345 reference statements)
8
121
0
4
Order By: Relevance
“…Metals have been studied for a long time in order to understand pathogenic mechanisms underlying development of neurodegenerative disease better, and to date there are prospects of study for this topic [71]. As for cadmium, apart from recent evidence of a high metal concentration in the cerebrospinal fluid of ALS patients [85], there are some works focusing on occupational exposures in certain employment sectors, such as production of nickel-cadmium batteries [86,87]. Some evidence in experimental models concerning neurotoxicity of other metals such as zinc and copper [88,89] is also present in scientific literature, but there is no strong evidence concerning relationship with ALS.…”
Section: Discussionmentioning
confidence: 99%
“…Metals have been studied for a long time in order to understand pathogenic mechanisms underlying development of neurodegenerative disease better, and to date there are prospects of study for this topic [71]. As for cadmium, apart from recent evidence of a high metal concentration in the cerebrospinal fluid of ALS patients [85], there are some works focusing on occupational exposures in certain employment sectors, such as production of nickel-cadmium batteries [86,87]. Some evidence in experimental models concerning neurotoxicity of other metals such as zinc and copper [88,89] is also present in scientific literature, but there is no strong evidence concerning relationship with ALS.…”
Section: Discussionmentioning
confidence: 99%
“…Corroborating this, Roos et al (37) found low plasma zinc content in patients with ALS. Moreover, Peters et al (38), in a case-control study, observed an inverse association between serum zinc concentration and ALS.…”
Section: Discussionmentioning
confidence: 83%
“…Dejenerasyonun sebebi bilinmemekle birlikte genetik, viral, travmatik ve çevresel mekanizmalar üzerinde durulmaktadır. 38 Metal toksisitesinin ALS ve diğer nörodejeneratif hastalıklarda risk faktörü olduğu düşünülse de 321 hastanın değerlendirildiği retrospektif bir çalışmada, idrar Al düzeylerinin normal sınırlar içinde olduğu bildirilmiştir. 39 ALS tanısı olan beş hastanın ventral servikal spinal kord örnekleri alınarak Al, Ca ve Fe düzeyleri ölçüldüğünde, Al düzeylerinin kontrole göre fark göstermediği, sadece Fe düzeylerin yük-sek olduğu saptanmıştır.…”
Section: Amyotrofi̇k Lateral Sklerozunclassified
“…Sonuçlar ALS patogenezinde nörotoksik metallerin etkisini güçlendir-miştir. 38 Diğer taraftan ALS tanısı olan beş hasta- 43 Yapılan bu çalışmalar toksik metallerin hastalığın patofizyolojisindeki rolünü desteklemektedir.…”
Section: Amyotrofi̇k Lateral Sklerozunclassified